Ouvrir la boîte noire du capital culturel - Frédérique Giraud (Recherches Sociologiques et Anthropologiques)
Frédérique Giraud’s article analyzes the transmission of cultural capital within families through the use of Montessori games and books, showing that this transmission is neither automatic nor a matter of simple inheritance. Instead, it requires continuous parental investment and intentional action. Contrary to the idea of a diffuse “cultural bath,” this is a deliberate process in which games, objects, and everyday learning activities become tools of socialization – well beyond the realm of legitimate cultural practices. A qualitative study of 65 families reveals that working-class households use Montessori materials to address academic difficulties and foster autonomy, while middle- and upper-class families use them to reinforce academic advancement and develop distinctive skills, transforming their domestic space into a learning environment. The article thus demonstrates that differences in cultural capital are not only about the possession of objects or skills, but also about how they are used and valued – challenging the notion of passive transmission and highlighting the central role of parental educational labor.